Pengaturan Makan dan Aktivitas Olahraga Berhubungan dengan Pengontrolan Gula Darah pada Pasien Diabetes di Puskesmas Kecamatan Grogol Petamburan - Hidhayanti, Sirly; Kartini, Kartini (Jurnal Biomedika dan Kesehatan, 2024)
Background Diabetes Mellitus (DM) is a disorder of the body's metabolism with the main characteristic of which is increased blood glucose levels caused by interference of insulin secretion and action. One of the efforts to prevent complication is to check and control blood glucose levels in DM patients. To monitor blood glucose levels requires non-pharmacological management, such as eating arrangements and exercise activities. This study aim was to assess the association between eating arrangements and exercise activities with blood sugar control in adult diabetic patients. Methods Study desain was an observational analytic with a cross-sectional approach. Study was conducted at Grogol Petamburan Health Center, in September-November 2022, as many as 63 diabetes patients aged 18-60 years were selected consecutively by taking into inclusion and exclusion criteria. Data were collected using the 24 hours food recalls, Baecke Habitual Physical Activity Questionnaire and measuring non-fasting blood sugar levels. Statistical analysis using Chi – Square test with a significance level of p <0.05. Results Age of the subjects ranged from 41-50 years as many as 47.6%  and 69.8% were women, as many as 50.8% had a normal BMI.  Subjects who did not make meal arrangements as many as 63.5% and 50.8% were categorized as active in sports activities. Subjects with uncontrolled GDS levels were 52.4%. The Chi-Square test to assess the association between eating regulation and exercise activity with blood sugar control in adult diabetic patients showed p = 0.009 and p = 0.000. Conclusions Dietary arrangements and exercise activities were associated with blood sugar control in adult diabetic patients.